Rational Expectations, Econometric Exogeneity, and Consumption - Sargent, Thomas J. (Journal of Political Economy, 1978)
Estimates of a rational expectations version of Friedman's time-series consumption model are obtained by imposing the pertinent restrictions across the stochastic processes for consumption and income. A likelihood ratio test is used to test the adequacy of three joint hypotheses: namely, Friedman's model, rational expectations, and some arbitrary conditions on the disturbance process in the consumption function. The paper treats both the cases in which income is econometrically exogenous with respect to consumption and those in which it is not. The macroeconomics of this exogeneity condition are briefly discussed.